The Concept of “Merdeka Belajar” in the Perspective of Humanistic Learning Theory - Dewi Juita; Yusmaridi M (Universitas Negeri Padang, 2021)
The Minister of Education and Culture and his staff are trying to liberate teachers and students. Teachers are given the opportunity to explore their potential and their students. Teachers and students are given the freedom to think and determine the appropriate method in achieving learning objectives. The diversity of the abilities of students does not make students a source of self-doubt, but serves as benchmarks for teachers in building teacher gives freedom to students in choosing the methods and materials they need. Students are fully responsible for the educational process. The concept of “Merdeka Belajar” with humanistic theory along with its objectives the abilities of their students in a positive direction. Teachers are no longer burdened with administrative tasks that hinder teacher creativity. Humanistic learning theory has the aim of humanizing humans. The implementation, and evaluation. The goal to be achieved is to humanize humans and explore and develop the potential of teachers and students. Implementation of learning refers to meaningful learning that prioritizes the needs of students in real life. Learning evaluation is also carried out thoroughly and comprehensively.Keywords: Merdeka Belajar, Humanistic Theory